Impact of estradiol monitoring on the prediction of intrauterine insemination outcome - Ozkan, Zehra Sema; Ilhan, Rasit; Ekinci, Mustafa; Timurkan, Huseyin; Sapmaz, Ekrem (Elsevier Science Bv, 2014)
Objective: To evaluate the predictive value of oestradiol levels on the day of human chorionic gonadotrophin (hCG) administration on intrauterine insemination success rate. Methods: The present study included 206 intrauterine insemination (IUI) cycles performed between June 2011 and October 2012. All IUI cycles were preceded by ovarian stimulation with gonadotrophins starting on cycle day 3. A single IUI was performed 24-36 h after hCG administration. Binary logistic regression analysis was performed to define the covariates of IUI success. The main outcome measure, clinical pregnancy rate per cycle, was assessed according to the oestradiol level. Results: With LR + = 2 and AUC = 0.73, ROC analysis revealed out the oestradiol level as 465 pg/mL to predict the pregnancy with 60% sensitivity and 66% specificity. Binary logistic regression analysis identified the presence of oestradiol levels higher than 465 pg/mL (p < 0.01, 95% CI = 0.147-0.687) and stimulation duration (p < 0.01, 95% CI = 0.201-0.705) as the covariates approached statistical significance for IUI success. Conclusions: Oestradiol level >465 pg/mL on the day of hCG administration might point out advanced outcome on mild ovarian stimulation combined with insemination.
Keywords: Intrauterine insemination; Oestradiol level; Outcome; Pregancy rate